FREQUENCY OF THROMBOCYTOPENIA AMONG PATIENTS WITH CIRRHOSIS - MAAZ, .; HAMEED , A; SHAH , S; MAZARI , N; SHABBIR , Y (Biological and Clinical Sciences Research Journal, 2024)
Thrombocytopenia is a frequently observed condition in individuals suffering from liver cirrhosis. Objective: To find out the frequency of thrombocytopenia in patients with cirrhosis. Methodology: This cross-sectional study was conducted in the Department of Medicine, Khyber Teaching Hospital, Peshawar, from January 2022 to January 2023. All patients with cirrhosis of duration > six months, with ages of 18-60 years, both genders, and any grade of cirrhosis severity were included in the study. Patients with diseases like malaria, dengue fever, ITP and haematological malignancy, SLE, leukaemia, aplastic anaemia, or on drugs like quinine, penicillin, and digoxin were excluded from the study. Platelet counts were done by sending blood to the hospital laboratory. Result: Mean age was 47.43 ± 6.22 years, mean BMI was 25.29 ± 4.06 kg/m2, and mean disease duration was 14.86 ± 5.36 years. Males were 75 (53.1%), and females were 67 (46.9%). Thrombocytopenia was present in 108 (75.5%) and not in 35 (24.5%) patients. There was no association of age, gender, or Child-Pugh score with the occurrence of thrombocytopenia. Still, the increased BMI and increased disease duration were significantly associated with thrombocytopenia (p-value <0.05). Conclusion: There is quite a high prevalence of thrombocytopenia in patients with liver cirrhosis. The duration of the disease and increased BMI are significantly associated with the occurrence of thrombocytopenia. Further studies are recommended to have further proof.